Horizontal Well Perforation Section and Perforation Cluster Optimization Based on Fiber Optic Temperature Monitoring Technology - SHI Limei; AN Jixing; WEI Bing; YU Jiahui; XING Chengjingyu; WANG Xi (Cejing jishu)
At present, the single well output of horizontal wells in Qian ’an area of Jilin oilfield can only be obtained by the total production capacity data. It is impossible to make a precise evaluation of the productivity contribution of the perforation section and perforation cluster after fracturing. There is no monitoring data as data support. It is impossible to form a reservoir evaluation standard combining geological dessert and engineering dessert. In order to solve the problems, optical fiber temperature monitoring equipment is embedded in horizontal wells to monitor the temperature profile characteristics of horizontal wells in real time, and to effectively evaluate the oil production and changes of each section and cluster after fracturing. The method can provide data support for analyzing the productivity contribution of each fractured reservoir. Based on the principle and interpretation method of optical fiber temperature monitoring technology, the logging parameters and fracturing parameters (fracture pressure, sand addition) are used to evaluate the optical fiber productivity. The exponential model evaluation formula and productivity interpretation chart and standard of logging parameters and fracturing parameters are established, which realized the double optimal selection of geological dessert and engineering dessert. The effective optimization of perforation section and perforation cluster is realized by reducing the length of perforation section, increasing the number of perforation clusters and shortening the spacing of clusters. The application of optical fiber temperature monitoring technology in unconventional horizontal wells in Qian ’an area of Jilin oilfield shows that, the use of monitoring data to evaluate the productivity contribution of perforation sections and perforation clusters is beneficial to optimize the design of horizontal well fracturing schemes.